N.V. Gordienko, N.V. Semenchuk PSYCHOLOGICAL AND PEDAGOGICALSUPPORT OF FORMATION OF PROFESSIONAL CONSCIOUSNESS OF PROFESSIONAL (PROFESSIONAL-TECHNICAL) EDUCATION INSTITUTIONS: professional education; psychological and pedagogical support; psychological monitoring; psychological readiness; employment - Hordiienko, Nataliia; Semenchuk, Nadiia (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
The article presents the results of a study of psychological readiness for employment of students of vocational (vocational) education. The purpose of the study is to substantiate the need and importance of psychological and pedagogicalsupport for the formation of professional consciousness as an important aspect of becoming a specialist in the system of professional (vocational) education.Psychological and pedagogical support of the formation of professional consciousness in students of vocational (vocational) education throughout the training period includes diagnostic, correctional, educational and counseling work of a practical psychologist.The study used a set of theoretical and empirical methods, which made it possible to determine the levels of professional consciousness in students of the first and third courses of the integrated profession "mechanic for the repair of wheeled vehicles; driver of category "B", "C" and for first- and third-year students of the integrated profession “computer set operator; electrician for maintenance and repair of LAN". The psychological readiness of graduates of final courses at the final stage of training to the beginning of labor activity is investigated.Results. It is proved that the psychological readiness for the beginning of labor activity of future skilled workers, competitive in the modern labor market, depends on their level of formation of professional consciousness. Conclusions. Thus, due to the implementation of professional (vocational) education in the institution of psychological support of the formation of professional consciousness, students at the final stage of training are psychologically ready to start working.It is also at the level of vocational (vocational) education institutions, the psychological readiness of students from among graduates of institutions for employment was monitored. The issues of formation of professional consciousness during the meetings of pedagogical councils of institutions, meetings of methodical commissions of professional orientation, meetings of the school of professional skills of masters of industrial training, etc